The role of social relationship functioning in suicidal ideation among adolescents at-risk for adult obesity - Elliker, Elyse, author; Shomaker, Lauren, advisor; Lucas-Thompson, Rachel, committee member; Brown, Samantha, committee member (Colorado State University. Libraries, 2020)
Prevalence of child and adolescent obesity represents a public health crisis in the United States and globally. Having tripled over the last 50 years, current rates of obesity show that approximately 18% of children aged 2-19 years in the United States are affected. While metabolic health consequences of obesity are of great concern, including insulin resistance and impaired glucose, obesity also is related to a range of adverse psychological concerns, including depression and suicidal ideation. Indeed, there has been an alarming rise in adolescent suicidal ideation and behavior, and a possibility that heavier youth are at higher risk. Yet, theoretical and empirical data support the possibility that positive social relationship functioning may play an important moderating role, by buffering the effects of weight discrimination on suicidal ideation in youth with overweight and obesity. In the current master's thesis proposal, I conducted a secondary analysis of the cross-sectional associations among social relationship functioning, suicidal ideation, and metabolic health characteristics in 90 adolescents aged 12-17 years (50% girls) at-risk for adult obesity. Adolescents completed survey measures of social relationship functioning and survey/interview measures of depression and suicidal ideation. Height and fasting weight were collected to determine body mass index (BMI) indices, and body fat was measured via air displacement plethysmography. A fasting blood sample was analyzed for fasting insulin, fasting glucose, and insulin resistance. I explored the bivariate associations among social functioning, depression, BMI, metabolic indices, and without suicidal ideation. Then I tested BMI/metabolic indices, social relationship functioning, and their interactions as a predictor of suicidal ideation, controlling for depression symptoms in order to evaluate the unique relation of BMI/metabolic indices and social functioning with suicide ideation. Nearly 30% of adolescents reported suicidal ideation. Contrary to hypotheses, results showed that neither BMI/body fat nor metabolic indices were related to suicidal ideation, nor did social act as a moderator of these associations. Accounting for age, sex, and BMI z, depression was robustly related to higher odds of suicidal ideation. Most dimensions of social functioning related in bivariate analyses to suicidal ideation, and some dimensions, even when accounting for depression symptoms and other covariates, showed a trend-level or significant association with suicidal ideation. These results point to the prevalence of suicidal ideation in adolescents at risk for adult obesity and suggest that elevated depression symptoms are the primary marker of risk for suicidal ideation in this population. Additional research with larger samples and longitudinal data are needed to further test the role of social functioning in mitigating, or perhaps mediating, suicidal ideation risk in adolescents at risk for adult obesity, as well as research into other possible protective factors.
Keywords: obesity; suicide; social functioning; adolescent